지역 내 준거집단과 비교한 경제적 격차가 삶의 만족감에 미치는 영향에 대한 연구 - 임보영(Im, Bo-Yeong); 마강래(Ma, Kang-Rae) (국토계획, 2015)
An ever-growing number of studies have investigated whether individual Subjective Well-Being(SWB) varies not only with one’s own absolute income but also the incomes of others. Some of them have tried to define what is known as the reference groups which may include all members of society or only a subgroup. Previous studies, however, have not paid much attention on the spatial context when they examine the influence of the income of a reference group on individual SWB. The main purpose of this study is to examine the relationship between individual SWB and relative deprivation level of income (or consumption) in the same administrative areas, using the data from the Korean Labor & Income Panel Study(KLIPS). The main findings are that first, both absolute and relative income (or consumption) have a significant effect on the individual SWB. Second, consumption variable shows much higher statistical significance on the SWB than income variable, which means that compared to the latter variable, individual SWB is more sensitive to the former one. Third, individuals who live in wealthier regions are more likely to report a lower level of SWB than those in the rest of the regions. KCI Citation Count: 11